The Impact of Target Costing and TD-ABC on Cost Reduction and Corporate Competitiveness - Imad Nayef Turki; Hamad Abd Mustafa; Waseem Saleh Khalaf (International Journal of Economics, Commerce, and Management, 2025)
This research examines how cost characteristics influence the relationship between target costing and time-driven activity-based costing (TDABC) approaches and their subsequent impact on corporate competitiveness. Using a descriptive analytical approach, the researcher collected data through a structured questionnaire, which was then processed and analyzed using SPSS software. The study aimed to test the validity of the proposed hypothesis, which suggested that a standalone approach—either target costing or TDABC—fails to sufficiently enhance competitiveness. However, the integration of both approaches proved to be beneficial, allowing companies to improve their competitive positioning by reducing overall costs. The research concludes that combining target costing and TDABC can create synergies that better align with the goal of cost reduction. As a recommendation, companies are encouraged to integrate these cost management approaches to maximize their competitive advantage in the market and optimize cost efficiency.